2010
DOI: 10.1016/j.neuron.2010.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Stimulation Promotes BDNF-Dependent Synaptic Plasticity: Potential Implications for Motor Learning

Abstract: SUMMARY Despite its increasing use in experimental and clinical settings, the cellular and molecular mechanisms underlying transcranial direct current stimulation (tDCS) remain unknown. Anodal tDCS applied to human motor cortex (M1) improves motor skill learning. Here, we demonstrate in mouse M1 slices that DCS induces a long-lasting synaptic potentiation (DCS-LTP), which is polarity-specific, NMDA-receptor dependent and requires coupling of DCS with repetitive low-frequency synaptic activation (LFS). Combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
1,099
4
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,247 publications
(1,175 citation statements)
references
References 41 publications
56
1,099
4
16
Order By: Relevance
“…Increased spontaneous neuronal firing and synaptic efficacy induced by direct‐current stimulation may strengthen neuronal connectivity through long‐term potentiation‐like mechanisms41, 42, 43. These mechanisms may potentiate motor learning, which is also thought to depend on long‐term potentiation‐like plasticity occurring in the motor cortex44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased spontaneous neuronal firing and synaptic efficacy induced by direct‐current stimulation may strengthen neuronal connectivity through long‐term potentiation‐like mechanisms41, 42, 43. These mechanisms may potentiate motor learning, which is also thought to depend on long‐term potentiation‐like plasticity occurring in the motor cortex44.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of the motor network, including the primary motor cortex, premotor cortex, supplementary motor areas and basal ganglia, has been implemented in motor learning45 46. Modulated synaptic efficacy43 and cortical connectivity47 between these regions may facilitate tDCS‐enhanced motor learning. It is also important to consider that the tDCS montage applied here involved passing current through a large anode to a large cathode.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, variants of the same basic task may assess very different learning processes. This may be particularly important for a technique like tDCS (which may exert its effect through the alteration of thresholds for neuronal discharge (Fritsch et al, 2010)) as observed effects may be highly dependent on the specific context in which it is applied. Currently, the most frequently used tasks to investigate motor skill learning in experimental settings are: (1) sequential finger tapping tasks (SFTT; which can include either implicit or explicit sequence structure) (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Nitsche et al, 2010;Reis et al, 2015;Song & Cohen, 2014); and (2) the sequential visual isometric pinch force task (SVIPT) (Reis et al, 2009).…”
Section: Motor Learningmentioning
confidence: 99%
“…Using the same task, Bastani & Jaberzadeh (2014) investigated the effect of repeated offline application (up to 3) of relatively low intensity (0.2 mA) and duration (10 min) anodal tDCS to the dominant (left) M1 on corticospinal excitability and behavior (Bastani & Jaberzadeh, 2014). Not surprisingly, given our understanding of the need for synchronous application of tDCS with training (Fritsch et al, 2010), no behavioral effects were observed. Of note however, corticospinal excitability was significantly facilitated up to 24 hours depending on the interval between subsequent stimulation applications, which had been reported previously .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
See 1 more Smart Citation